2021
DOI: 10.37190/ppmp/133833
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and kinetic study of zinc leaching from metallurgical slag by 5-sulfosalicylic acid

Abstract: As an organic acid with the characters of low corrosivity and extensive source, 5-sulfosalicylic acid (5-SSA) was firstly utilized as a potential leaching reagent for the recovery of zinc from metallurgical slag. Effects of stirring speed, leaching temperature, 5-SSA concentrations and size fraction on the leaching zinc leaching rate were investigated. A zinc leaching efficiency of 94.2% was achieved under the appropriate operating conditions (450 rpm of stirring speed, 50 ℃ of leaching temperature, 0.3 mol/L … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 41 publications
0
3
0
Order By: Relevance
“…To quantitatively describe the influence of the liquid-solid ratio and leaching temperature on the kinetics of zinc leaching, a semi-empirical equation was proposed, as follows [23,24]:…”
Section: Leaching Kinetic Equationmentioning
confidence: 99%
“…To quantitatively describe the influence of the liquid-solid ratio and leaching temperature on the kinetics of zinc leaching, a semi-empirical equation was proposed, as follows [23,24]:…”
Section: Leaching Kinetic Equationmentioning
confidence: 99%
“…The inorganic acid leaching method, which utilizes an inorganic acid such as sulfuric acid, consumes a large amount of acid and produces a silica gel that is difficult to treat [13][14][15][16][17]. Organic acids are biodegradable and can reduce environmental pollution, making them a good choice as a leaching agent for zinc extraction [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…The grade of the resulting magnetic fraction was 90.59% Fe with an iron recovery of 50.87%. In another investigation [36], it was shown that the pelletizing process is more suitable for recovering valuable metals from jarosite residues through direct reduction. The decomposition of zinc ferrite into ZnO and Fe 3 O 4 using a mixture of CO and Ar gas as reducing agents were investigated [37].…”
Section: Introductionmentioning
confidence: 99%